2015
DOI: 10.1371/journal.pone.0143469
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a Friendship? Partner Visibility Supports Cognitive Collaboration between Friends

Abstract: Not all cognitive collaborations are equally effective. We tested whether friendship and communication influenced collaborative efficiency by randomly assigning participants to complete a cognitive task with a friend or non-friend, while visible to their partner or separated by a partition. Collaborative efficiency was indexed by comparing each pair’s performance to an optimal individual performance model of the same two people. The outcome was a strong interaction between friendship and partner visibility. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…For example, such a measure could be applied across a company to achieve success among colleagues who are unfamiliar with each other or are from different departments, but need to collaborate on a task. On the other hand, Brennan and Enns (2015) found a relationship between familiarity and visibility of a partner when performing a visuospatial task. Familiar pairs were reported to outperform unfamiliar pairs when visible to each other, but when separated by a partition, familiar and unfamiliar pairs performed similarly.…”
Section: Discussionmentioning
confidence: 96%
“…For example, such a measure could be applied across a company to achieve success among colleagues who are unfamiliar with each other or are from different departments, but need to collaborate on a task. On the other hand, Brennan and Enns (2015) found a relationship between familiarity and visibility of a partner when performing a visuospatial task. Familiar pairs were reported to outperform unfamiliar pairs when visible to each other, but when separated by a partition, familiar and unfamiliar pairs performed similarly.…”
Section: Discussionmentioning
confidence: 96%
“…For example, such a measure could be applied across a company to achieve success among colleagues who are unfamiliar with each other or are from different departments, but need to collaborate on a task. On the other hand, Brennan and Enns () found a relationship between familiarity and visibility of a partner when performing a joint visual search task. Familiar pairs were reported to outperform unfamiliar pairs when visible to each other, but when separated by a partition, familiar and unfamiliar pairs performed similarly.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a different study, Brennan and Enns found that dyads in a joint visual search task who were allowed to verbally communicate were still able to reach a collective benefit and attain a collaborative benefit. In a follow‐up study, Brennan and Enns extended their work and investigated how the social relation between members of a group (i.e., if they are friends or not) can affect the joint performance. They found that friends outperformed nonfriends if they were visible to each other, suggesting that the social relationship between members of a group is another factor that affects joint performance.…”
Section: Joint Visuospatial Tasksmentioning
confidence: 99%